Recent Developments of the Synthetic Biology Toolkit for Clostridium - Joseph, Rochelle C.; Kim, Nancy M.; Sandoval, Nicholas R. (Frontiers in Microbiology, 2018)
The Clostridium genus is a large, diverse group consisting of Gram-positive, spore-forming, obligate anaerobic firmicutes. Among this group are historically notorious pathogens as well as several industrially relevant species with the ability to produce chemical commodities, particularly biofuels, from renewable biomass. Additionally, other species are studied for their potential use as therapeutics. Although metabolic engineering and synthetic biology have been instrumental in improving product tolerance, titer, yields, and feed stock consumption capabilities in several organisms, low transformation efficiencies and lack of synthetic biology tools and genetic parts make metabolic engineering within the Clostridium genus difficult. Progress has recently been made to overcome challenges associated with engineering various Clostridium spp. For example, developments in CRISPR tools in multiple species and strains allow greater capability to produce edits with greater precision, faster, and with higher efficiencies. In this mini-review, we will highlight these recent advances and compare them to established methods for genetic engineering in Clostridium. In addition, we discuss the current state and development of Clostridium-based promoters (constitutive and inducible) and reporters. Future progress in this area will enable more rapid development of strain engineering, which would allow for the industrial exploitation of Clostridium for several applications including bioproduction of several commodity products.